Some methods of fish capture in the Philippines. - Miclat, Emiliano M. (College of Fisheries, University of the Philippines, 1954)
The reports attached here are based on actual participation and observation on during my apprenticeship actual fishing conditions, operations and all problems relative to the functions of a fishing concern were observed on board regular commercial fishing vessels and in some waters of the Philippines. The better part of the discussions is centered on the bag net (bansig) gear wherein I spent the most part of my training. The outfit is owned by an operator of Navotas, Rizal, and fished mostly in Palawan waters. I consider the training I got during this apprenticeship as monumental in my career, especially in pelagic fishing. The training greatly added to my theoretical studies in the classrooms of the Philippine institute of fisheries technology. I am hoping that these repots will not only help me, but also those who are interested in joining the fishing industry.